EDITORIAL - Jacinto Pazos, Pedro (2020)
We explain this because of the harsh competitiveness involved in the commercial product, which also involves the movement of mechanized financial capitals that are offered worldwide, where we warn that only the great commercial powers of the United States, China, Russia and the European Union They come into play. It is the bleak landscape in which we seek our space as a Peruvian society and as an academic world, where at least they let us think about our hopes, our dreams or our utopias. And we say this, because it is the context on which our Ricardo Palma University enters its fifties and at the same time guides us towards the bicentenary of our Peruvian emancipation. And in which the SCIENTIA Magazine is part of this process. Then, we can say, that the last twenty years we have put it in evidence and made it shine in large part of the research that has been published in all our numbers. We believe that world belligerence can only be obstructed and defeated with research, knowledge and humanism. And there is the role of SCIENTIA to fulfill this great objective.